The Gospel according to Moses : what my Jewish friends taught me about Jesus - Dickson, Athol, 1955- (Grand Rapids, Mich. : Brazos Press, 2003)
"'The Gospel according to Moses' is refreshingly eloquent and deeply personal. It will attract devout Christians and Jews who wish to better understand their historical and biblical relationship. Its Socratic tone makes it a wonderful teaching tool for clergymen, teachers, and Bible study leaders"--The publisher.
Dealing with doubts -- Finding meaning in monotheism -- Why God lets me suffer -- Understanding scriptural paradox -- Approaching the God of "fire and brimstone" -- Why it is so easy to be bad -- Finding connections between obedience and God's grace -- Christians and the law of Moses -- Reconciliation with God -- Evil Christians in spite of Jesus -- The trinity and monotheism -- Jesus in the Hebrew scriptures -- Are Jews going to hell?
Includes bibliographical references.
Keywords: Theology, Doctrinal; Christian life -- Biblical teaching; Bible -- Relation to the Pentateuch; Bible. -- Relation to the New Testament; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Bible. A.T. Pentateuque; Bible